2000
DOI: 10.1159/000014419
|View full text |Cite
|
Sign up to set email alerts
|

Microbiologic Purity of Dialysate:Rationale and Te chnical Aspects

Abstract: Dialysate purity has become a major concern in hemodialysis since it has been shown that microbial-derived products were stimulating the production and the release of proinflammatory cytokines in hemodialysis patients. This chronic microinflammatory state induced by hemodialysis has been putatively implicated in the development of dialysis-related pathology. In order to prevent risk related to these offenders and to reduce patient/dialysis interaction, it appears highly desirable to use ultrapure dialysis flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 48 publications
4
25
0
Order By: Relevance
“…In agreement with previous studies, this suggests that hemodialysis water, even with acceptable levels of bacterial contamination, is capable of inducing inflammatory activity (27,28), although this subject is still being debated (29,30). Schiffl and colleagues (31) demonstrated that the use of ultrapure water leads to the improvement of inflammatory and nutritional parameters.…”
Section: Discussionsupporting
confidence: 89%
“…In agreement with previous studies, this suggests that hemodialysis water, even with acceptable levels of bacterial contamination, is capable of inducing inflammatory activity (27,28), although this subject is still being debated (29,30). Schiffl and colleagues (31) demonstrated that the use of ultrapure water leads to the improvement of inflammatory and nutritional parameters.…”
Section: Discussionsupporting
confidence: 89%
“…The latter is one of the major components of the hemocompatibility network in HD patients and is identified as a risk factor in the dialysis-related pathology [17]. OL HDF uses ultrapure dialysate and reinfusate with the aim of sterility and apyrogenicity and thus contributes to a reduced proinflammatory cytokine production, improving anemia.…”
Section: Discussionmentioning
confidence: 99%
“…On-line preparation of intravenous substitution fluid is a safe procedure, as it gives access to virtually unlimited amounts of a sterile and nonpyrogenic solution [17]. Moreover on-line-prepared dialysate and reinfusate for HDF can be considered safe regarding trace elements and micropollutants [18]; large volumes of reinfusate do not affect the plasma levels of trace elements [19].…”
Section: Introductionmentioning
confidence: 99%
“…At the time of data collection, all patients were treated by a sterile and nonpyrogenic dialysis fluid containing less than 100 colony forming units per liter (CFU/l), and less than 0.025 endotoxin units per ml (EU/ml) [10]. …”
Section: Methodsmentioning
confidence: 99%